Life on earth : the story of evolution - Jenkins, Steve, 1952- (Boston : Houghton Mifflin, 2002)
Provides an overview of the origin and evolution of life on earth and of what has been learned from the study of evolution.
Includes bibliographical references.
Five Owls.
School Library Journal starred.
Wilson's Children.
5.5
3-6
Keywords: Evolution (Biology) -- Juvenile literature; Evolution (Biology); Evolution